Respons Pertumbuhan Bibit Kakao (Theobroma cacao L.) Terhadap Pemberian Pupuk Organik Vermikompos dan Interval Waktu Penyiraman Air Pada Tanah Subsoil - Rizki Rinaldi Dalimunthe; Irsal Irsal; Meiriani Meiriani (Universitas Sumatera Utara, 2015)
The aim of this research was to determine growth response of cacao seedlings by givingvermicompost and watering time interval in the subsoil. The research had been conducted in theGreenhouse Faculty of Agriculture, University of Sumatera Utara, Medan on May 2013 untilAugust 2013 by using Randomized Block Design with two factors: vermicompost (0, 10, 20, 30%growth media volume) and watering time interval (1, 3, 5, and 7 days). The parameters observedwere plant height, stem diameter, total of leaf area, canopy fresh weight, canopy dry weight, rootfresh weight, root dry weight, root height, and water use efficiency. The results showed thatvermicompost has significant effects to plant height 4-14 WAP, stem diameter 4-14 WAP, total ofleaf area, root fresh weight, root height and water use efficiency but not significant to canopy freshweight, canopy dry weight and root dry weight. Watering time interval has significant effects toplant height 10, 12 and 14 WAP, stem diameter 8, 10, 12 and 14 MST, canopy fresh weight, canopydry weight,total of leaf area and water use efficiency but not significant to plant height 4, 6 and 8MST, stem diameter 4 and 6 WAP, root fresh weight, root dry weight, and root height.Theinteraction of vermicompost and watering interval had not significant.Keywords : vermicompost, Watering Time Interval, Cacao